2004
DOI: 10.1557/proc-845-aa1.8
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Guidance Cues Affect Fibroblast Cell Alignment: Electric Fields vs. Contact Guidance

Abstract: When bovine ligament fibroblast cells were cultured on parallel micro-grooved surfaces, they aligned their long axes parallel to the groove direction. This alignment was dependent on the groove depth, with increasing groove depth increasing guided cell alignment. When cells were cultured in a physiological dc electric field (EF) on non-grooved, flat surfaces, the cells aligned in response to the EF, with their long axes perpendicular to the EF vector. This response was EF strength dependent, increasing EF stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The predicted angle-dependence as well as the predicted addition of normalized guiding signals (Eq. C8) is verified for fibroblasts exposed to electric field and grooved surfaces (data from (33)). For single cues one gets K hL ¼ 12 and K E ¼ 0.025 mm/mV.…”
Section: Appendix C: Several Guiding Signalsmentioning
confidence: 83%
See 1 more Smart Citation
“…The predicted angle-dependence as well as the predicted addition of normalized guiding signals (Eq. C8) is verified for fibroblasts exposed to electric field and grooved surfaces (data from (33)). For single cues one gets K hL ¼ 12 and K E ¼ 0.025 mm/mV.…”
Section: Appendix C: Several Guiding Signalsmentioning
confidence: 83%
“…The signal strength characteristics, g(signal), predicted by the symmetry properties of the system, is the square of the cellular input signals: (hL) 2 , a strong indication that the symmetries are fulfilled. The measured general guiding coefficient K hL G is 24 for melanocytes and 12 for fibroblasts (33). Both cell types have a comparable cell size but the coefficient differs significantly.…”
Section: Signal Dependence To the Product Of Height And Line Densitymentioning
confidence: 94%
“…We observed that HDFs displayed a moderate preference for aligning with the direction in which the slides were dipped during the dip coating process (Figures 3B & 4). Cells without any preferential alignment would be expected to have an average orientation of 45° (Figures 3B & 4 & Supplementary Figure 2); however, we saw that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 38.6° ± 1.5° (Figure 4A & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 35.3° ± 1.8° (Figure 4B & E), which is likely to be because the polymer chains were aligned during the dip coating process as is commonly observed for multilayer films prepared in this fashion [34], and fibroblasts are known to respond to features on such length scales [35,36]. Interestingly, electrical stimulation of HDFs on the conductive substrates led to an increase in their propensity to align with the direction of the DC current passed through the substrate (akin to their behavior when a DC current is passed through the culture medium) [37], and we found that HDFs on PEDOT-PSS-based multilayer films had an average orientation of 27.7° ± 1.7° (Figure 4C & E), whereas HDFs on PEDOT-S-based multilayer films had an average orientation of 32.1° ± 1.1° (Figure 4C & E).…”
Section: Resultsmentioning
confidence: 99%
“…To assist cell adhesion, surfaces used as channels for cell seeding are often coated with ECM proteins (e.g. laminin, fibronectin, collagen) [65][66][67][68][69][70] and to improve cell motility and alignment, microgrooves are etched onto glass / quartz slides [71][72][73].…”
Section: Galvanotaxis Chambermentioning
confidence: 99%